التكيف المدرسي لدى نحو صعوبات التعلم في مادة الرياضيات المتمدرسين بالسنة الرابعة والخامسة ابتدائي - لعيدي, وردية (كلية العلوم الاجتماعية, 2025)
هدفت الدراسة الحالية إلى كشف مظاهر التكيف المدرسي لدى عينة مكونة من 60 استاذ الذين يدرون بالسنة الرابعة والخامسة لديهم صعوبات تعلم الرياضيات بالتعليم الابتدائي بمقاطعة سيدي لخضر ولاية مستغانم خلال الموسم الدراسي 2024/2025، بالاعتماد على المنهج الوصفي وباستخدام استبيان موجه للمعلمين لقياس مظاهر التكيف المدرسي وعلاقتها بصعوبات تعلم الرياضيات، تم التوصل الى النتائج التالية: 1. تتمثل نسبة مشاكل تعلم الرياضيات لأفراد عينة الدراسة بنسبة 60%. 2. أبرز الصعوبات التي تواجه التلاميذ في تعلم مادة الرياضيات لدى عينة الدراسة هي صعوبة في فهم المسائل الحسابية وضعف في مهارات الحساب الأساسية. 3. يمكن التعرف على التلاميذ ذوي صعوبات التعلم في الرياضيات داخل القسم من خلال: ملاحظات الأساتذة او عبر نتائج التقييمات والاختبار التحصيلي. 4. تؤثر صعوبات تعلم الرياضيات على أداء التلميذ في المدرسة من خلال انخفاض مستوى التحصيل الدراسي، قلة المشاركة في الأنشطة الصفية، الثقة بالنفس والدافعية. 5. تتمثل مظاهر التلاميذ ذوي صعوبات تعلم الرياضيات مع البيئة الصفية في الانسحاب من التفاعل مع المعلم والزملاء، مضاعفة الجهد، القلق والإحباط في مادة الرياضيات. 6. الأساليب التي يستخدمها الأساتذة لمساعدة التلاميذ ذوي صعوبات التعلم في الرياضيات تبسيط الشروحات باستخدام امثلة عملية، الوسائل البصرية كالمجسمات والرسوم البيانية، والعمل في مجموعات صغيرة لدعم العمل الفردي. 7. استراتيجيات الدعم المتاحة في المدرسة متوسطة الفاعلية. 8. لا يتلقى غالبية الاساتذة دعمًا من الأخصائيين التربويين أو المستشارين النفسيين حول كيفية التعامل مع التلاميذ ذوي صعوبات التعلم. The current study aimed to explore the manifestations of school adaptation among a sample of 60 teachers who teach fourth- and fifth-year primary school students with mathematics learning difficulties in the Sidi Lakhdar district of Mostaganem province during the 2024/2025 academic year. Using a descriptive approach and a teacher questionnaire to measure manifestations of school adaptation and their relationship to mathematics learning difficulties, the following results were obtained: 1. The percentage of mathematics learning problems among the study sample was 60%. 2. The most prominent difficulties students faced in learning mathematics in the study sample were difficulty understanding arithmetic problems and weakness in basic arithmetic skills. 3. Students with mathematics learning difficulties can be identified within the classroom through: teacher observations or through assessment and achievement test results. 4. Mathematics learning difficulties impact student performance in school through low academic achievement, lack of participation in classroom activities, self-confidence, and motivation. 5. Students with learning difficulties in mathematics exhibit a disengagement from the classroom environment, including withdrawal from interaction with the teacher and peers, increased effort, anxiety, and frustration in mathematics. 6. Methods used by teachers to help students with learning difficulties in mathematics include simplifying explanations using practical examples, visual aids such as models and graphs, and working in small groups to support individual work. 7. Support strategies available in the school are moderately effective. 8. The majority of teachers do not receive support from educational specialists or psychological counselors on how to deal with students with learning difficulties.
دراسة ميدانية بابتدائيات ببلدية سيدي لخضر مستغانم
Keywords: التكيف المدرسي، صعوبات التعلم، مادة الرياضيات